METAL SULFIDE COMPLEXES AND CLUSTERS - Rickard D.; Iii G.W.L. (My University, 2006)
The metal chemistry of anoxic systems is dominated by reactions with reduced sulfur species. These reduced sulfur systems presently characterize the Earth’s subsurface and are occasionally important in marine and freshwater systems. In the first half of Earth history, of course, the surface environments were also anoxic and the reduced sulfur chemistry played an even more widespread role in the geochemistry of base metals.